Editorial note. Introduction to the Special Issue “Brain and Behavior: A Neuroscientific / Psychophysiological Approach”, in honor and memory of Prof. Jesús Gómez Amor - Espín López, Laura; Salvador, Alicia (Anales de Psicología / Annals of Psychology, 2021)
Editorial note in which the special theme is presented and a brief comment is made on the articles that compose it.